Engagement of preservice teachers in the assessment of their Work-Integrated Learning - Dlamini, Moeketsi Elias; Tsotetsi, Cias Thapelo (OpenED Network, 2024)
Work-Integrated Learning (WIL) stands as a formally supervised and assessed program designed for preservice teachers to apply and refine their teaching skills within school settings. This study addresses the inquiry of how to effectively involve preservice teachers in the assessment of their WIL experiences. Employing participatory action research (PAR) as the chosen methodology, the research engaged with nine preservice teachers actively involved in WIL, a teaching practice officer, and five teachers serving as mentors to the students. Data collection was performed utilizing the principles of free-attitude interviews and participant observation. The ensuing data underwent interpretation and analysis employing the framework of critical discourse analysis. The findings revealed a pronounced need for collaborative efforts among assessors, mentor teachers, lecturers, and preservice teachers. Establishing robust collaboration emerged as the most viable solution for engaging preservice teachers in the assessment of their Work-Integrated Learning experiences.
Keywords: Assessment; Teacher education institution; Work-integrated learning; Preservice teacher; Teaching practice officer